Reflections on Students’ Synchronous Learning to Engage Autonomous Learning - Khulaifiyah, Khulaifiyah; Prabowo, Andri Eko; Idayani, Andi; Nawir, Erna (Jurnal Paedagogy, 2025)
This study aimed to describe students’ autonomous learning after students experienced synchronous learning. This research used a quantitative approach with a descriptive method. The study’s instrument is questionnaire through Google Form. The questionnaires consist of 15 items about students autonomous learning during synchronous learning and 10 items about students’ opinion of implementation of autonomous learning during synchronous learning. The data is described from 100 respondents to by descriptive analysis approach. The finding of this study reveals that there were four activities among other which students get, namely getting information about learning objectives for each new topic in synchronous learning, having different learning strategies for each different subject, looking for supporting materials that suit their needs, getting motivation during the class and students carried out learning activities as stated in the course outline from the lecturer's lesson plan. In addition, students' synchronous learning has become one of the factors that has assisted them in encouraging individual learning or keeping them autonomous with the assistance of lecturers' instruction and learning sources.